Post-Traumatic Stress in Vitiligo Patients: A Neglected but Real-Existing Psychological Impairment - Liu JW; Tan Y; Chen T; Liu W; Qian YT; Ma DL (Dove Medical Press, 2022)
Jia-Wei Liu, Yan Tan, Tian Chen, Wei Liu, Yue-Tong Qian, Dong-Lai Ma Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Skin and Immune Diseases, Beijing, 100730, People's Republic of ChinaCorrespondence: Dong-Lai Ma, Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Skin and Immune Diseases, Beijing, 100730, People's Republic of China, Tel +86-10-69151543, Fax +86-10-69151502, Email mdonglai@sohu.comBackground: Vitiligo is the most common depigmentation disorder. This disease causes disfiguration and induces psychological burdens, leading to significantly impaired quality of life. Limited research about disease-related post-traumatic stress (PTS) has been conducted in vitiligo patients.Objective: To evaluate the prevalence, severity, and risk factors of post-traumatic stress in vitiligo patients.Methods: This case-control study was performed from January 2021 to April 2021. A survey questionnaire including baseline information, post-traumatic stress symptoms evaluation, life quality evaluation was conducted. According to the severity of post-traumatic stress symptoms, patients were grouped and compared. The logistic regression model was conducted to analyze the risk factors for post-traumatic stress disorder (PTSD).Results: A total of 337 patients were included. A 30.3% of vitiligo patients (102/337) in present cohort had PTS and 12.5% patients (42/337) were confirmed for developing into PTSD. The multivariate logistic regression revealed educational level